Long-term survival outcomes of neoadjuvant chemotherapy in stage II-III HR+/HER2- breast cancer - Jiaxing Liu; Likuan Tan; Hongyu Zhang; Chengzhi Ma; Gang Qin; Shaolong Huang; Yang Long; Feng-hui He; Yao Huang; Miao-Miao Jiao; Yufei Liu; Guanghui Wang (Scientific Reports)
Abstract Breast cancer is the most common malignant tumor among women worldwide. Hormone receptor-positive/HER2-negative (HR+/HER2-) breast cancer is the largest subgroup among these cases. The application of neoadjuvant chemotherapy (NACT) has rapidly increased in recent years, but its impact on long-term survival in HR+/HER2- breast cancer remains debated. This retrospective cohort study analyzed 21,299 stage II-III HR+/HER2- breast cancer patients from the SEER database (2010–2021), employing propensity score matching (PSM) to balance intergroup differences. Kaplan-Meier survival analysis and Cox proportional hazards regression were used to identify significant prognostic factors. Among 21,299 patients, 17.8% received NACT. After propensity score matching (PSM; n = 6,930), the NACT group still showed poorer OS (5-year 83.7% vs. 89.6%; 10-year 69.9% vs. 76.7%; P < 0.001) and BCSS (85.9% vs. 91.6%; 10-year 75.3% vs. 81.8%; P < 0.001). Multivariate analysis confirmed NACT as an independent risk factor for mortality (HR 1.44, 95% CI 1.30–1.59, p < 0.001). Notably, achieving Pathological Complete Response (pCR) (17.3% of NACT patients) did not improve survival, while non-pCR patients had worse outcomes than adjuvant chemotherapy (ACT) recipients (OS HR 1.58, BCSS HR 1.68, p < 0.001). Stratified analyses revealed consistent survival disadvantages for NACT in stage IIB–IIIC, T1–T3, and N0–N2 subgroups. For stage III patients undergoing Breast-Conserving Surgery(BCS), NACT was associated with significantly lower OS and BCSS compared to ACT. NACT in stage II-III HR+/HER2- breast cancer is associated with inferior long-term survival outcomes compared to ACT, particularly in patients with T1–T3 tumors or N0–N2 lymph node involvement. While NACT may enhance BCS rates, its use should be cautiously weighed against potential survival trade-offs. These findings highlight the need for personalized treatment strategies and further validation through prospective trials, especially given the limitations of retrospective SEER data.